Offene Grenzen? Migrationsregime und die Schwierigkeiten einer Kritik des Nationalismus - Scherr, Albert (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2013)
Nation-state based migration regimes have often fatal consequences. Their justification presupposes the superiority of nationally designed interests in relation to the needs and the human rights of migrants. As a result the legitimization of migration regimes is called into question, and open borders are reclaimed. In this paper positions are discussed which nevertheless try to justify the necessity of nation states and their migration regimes. Against this background it is argued that it is required to develop a critical perspective which avoids the apparent alternative, open borders or justification of existing migration regimes.